Effects of dapagliflozin on urinary metabolites in people with type 2 diabetes. Issue 11 (18th July 2019) - Mulder, Skander; Heerspink, Hiddo J. L.; Darshi, Manjula; Kim, Jiwan J.; Laverman, Gozewijn D.; Sharma, Kumar; Pena, Michelle J.
Abstract: Aim: To assess the effects of the sodium‐glucose co‐transporter‐2 (SGLT2) inhibitor dapagliflozin on a pre‐specified panel of 13 urinary metabolites linked to mitochondrial metabolism in people with type 2 diabetes and elevated urine albumin levels. Materials and methods: Urine and plasma samples were used from a double‐blind, randomized, placebo‐controlled crossover trial in 31 people with type 2 diabetes, with an albumin:creatinine ratio >100 mg/g, and who were on a stable dose of an angiotensin‐converting enzyme inhibitor or an angiotensin receptor blocker. Dapagliflozin or placebo treatment periods each lasted 6 weeks, with a 6‐week washout period in between. Urinary and plasma metabolites were quantified by gas‐chromatography mass spectrometry, corrected for creatinine level, and then combined into a single‐valued urinary metabolite index. Fractional excretion of the metabolites was calculated. Results: All 13 urinary metabolites were detectable. After 6 weeks of dapagliflozin therapy, nine of the 13 metabolites were significantly increased from baseline. The urinary metabolite index increased by 42% (95% confidence interval [CI] 8.5 to 85.6; P = .01) with placebo versus 121% (95% CI 69 to 189; P < .001) with dapaglifozin. The placebo‐adjusted effect was 56% (95% CI 11 to 118; P = .012). In plasma, seven of the 13 metabolites were detectable, and none was modified by dapagliflozin. Conclusions: Dapagliflozin significantly increased a panel of urinary metabolites previously linked to mitochondrial metabolism. These data support the hypothesis that SGLT2 inhibitors improve mitochondrial function, and improvements in mitochondrial function could be a mechanism for kidney protection. Future studies with longer treatment duration and clinical outcomes are needed to confirm the clinical impact of these findings.